Roles of TGF-β Signals in Endothelial-Mesenchymal Transition during Cardiac Fibrosis - Yasuhiro Yoshimatsu; Tetsuro Watabe (International Journal of Inflammation)
Most cardiac diseases caused by inflammation are associated with fibrosis in the heart. Fibrosis is characterized by the accumulation of fibroblasts and excess deposition of extracellular matrix (ECM), which results in the distorted organ architecture and function. Recent studies revealed that cardiac fibroblasts are heterogeneous with multiple origins. Endothelial-mesenchymal transition (EndMT) plays important roles in the formation of cardiac fibroblasts during pathological settings. EndMT is regulated by signaling pathways mediated by cytokines including transforming growth factor (TGF)-β. Better understanding of the mechanisms of the formation of cardiac fibroblasts via EndMT may provide an opportunity to develop therapeutic strategies to cure heart diseases.